Overview of the Utility of Using Telerehabilitation on Physiotherapy Services in Indonesia - Arif Pristianto, Wa Ode Muzdalyfah, Rita Setiyaningsih (South Eastern European Journal of Public Health, 2025)
Introduction: The development of digital technology has also brought changes to aspects of health services so the telemedicine system was developed. In physiotherapy services, this system is known as telerehabilitation or telephysio which uses digital communication technology media to carry out assessment, diagnose, intervention, evaluation, education, consultation and coaching. The emergence of the COVID-19 pandemic made implementing this system even more popular, including in Indonesia. Objectives: The objective of this study is to see an overview of the utility of using telerehabilitation in physiotherapy services in Indonesia. Methods: The research method is descriptive observational. Results: The results of this study show that the majority of physiotherapists using telerehabilitation in Indonesia are in the Jawa and Bali islands (69.0%). The largest specialization is pediatric physiotherapists (37.5%). Physiotherapists quite understand the advantages and disadvantages of this system, even though around 75.0% feel they are still more comfortable practicing with direct visits because they cannot examine patients as with direct visits. 93.8% stated that telerehabilitation will still be needed even though the COVID-19 pandemic is over. Conclusions: An overview of the utility of using telerehabilitation in physiotherapy services in Indonesia shows that this system has not been spread evenly throughout Indonesia and its implementation is still not significantly satisfactory